2018
DOI: 10.1016/j.jalz.2018.02.016
|View full text |Cite
|
Sign up to set email alerts
|

Identifying dementia cases with routinely collected health data: A systematic review

Abstract: IntroductionProspective, population-based studies can be rich resources for dementia research. Follow-up in many such studies is through linkage to routinely collected, coded health-care data sets. We evaluated the accuracy of these data sets for dementia case identification.MethodsWe systematically reviewed the literature for studies comparing dementia coding in routinely collected data sets to any expert-led reference standard. We recorded study characteristics and two accuracy measures—positive predictive v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
226
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(242 citation statements)
references
References 41 publications
7
226
3
Order By: Relevance
“…Of the 1,701 participants clinically diagnosed as not having dementia, 136 (8%) were misidentified in Medicare claims as having dementia. These results are consistent with the wide range of results reported …”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Of the 1,701 participants clinically diagnosed as not having dementia, 136 (8%) were misidentified in Medicare claims as having dementia. These results are consistent with the wide range of results reported …”
Section: Discussionmentioning
confidence: 72%
“…A recent review comparing the validity of dementia identification in administrative datasets with that of expert‐led reference standards such as a clinical diagnosis reported tremendous heterogeneity in sensitivity estimates, ranging from 21% to 86% . The majority of studies reported moderate sensitivity (40–50%) in detecting dementia, but several reported sensitivity estimates below 30% or as high as 80% .…”
mentioning
confidence: 99%
“…The use of primary care data to determine number of cases can be problematic in that dementia may be underrecognised and underreported . There is evidence that the identification of dementia cases from routine health records has high positive predictive value and reasonable sensitivity . By using CFAS II estimates specific to CCG area, we have been able to include estimates of unknown cases …”
Section: Discussionmentioning
confidence: 99%
“…That is, individuals with and without dementia at or before index hospitalization were separated into distinct cohorts to allow investigation of emergence of dementia in those not previously diagnosed, and then progression of dementia to death among those who had been previously diagnosed. Diagnosis was ascertained using clinical billing data in terms of the International Statistical Classification of Diseases and Related Health Problems, versions 9 and 10 codes as well as structured problem list codes for dementia …”
Section: Methodsmentioning
confidence: 99%